Influence of Feeding Omega-3 Polyunsaturated Fatty Acids to Broiler Breeders on Indices of Immunocompetence, Gastrointestinal, and Skeletal Development in Broiler Chickens - Thanabalan, Aizwarya; Kiarie, Elijah G. (Frontiers in Veterinary Science, 2021)
Modern broiler chickens are associated with rapid growth rates and superior feed efficiency. However, they are susceptible to physiological and metabolic disorders (e.g. skin lesions, lameness, sudden death, enteric diseases, myopathies) that exert substantial economic losses to producers. This is further exacerbated by consumer pressure and mandated cessation of production practices such as indiscriminate use of preventative antimicrobial growth promoters. Manipulation of broiler breeder (BB) nutrition and management can influence chick quality, robustness, and resilience to stressors in the production environment. The present review examines the role of feeding BB functional polyunsaturated omega–3 fatty acids (n-3 PUFA) and subsequent impact on the indices of immunocompetence, skeletal and gastrointestinal (GIT) development in broiler chickens. Research in mammalian and avian models led evidence that perinatal feeding of long chain ω-3 PUFA such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) engender transgenerational effects through regulation of a variety of biological processes including development of vital organs such as skeleton, brain and GIT. It has been shown that feeding poultry breeders n-3 PUFA decreased inflammatory state and enriched hatching eggs with n-3 PUFA and immunoglobulins. Further evidence has shown that after 15 days of incubation, chicken embryo preferentially utilized long chain n-3 PUFA critical for optimal cell, tissues and organs development. Enrichment of n-3 PUFA in newly hatched chicks' tissues reduced proinflammatory eicosanoids with consequences of enhanced bone mineralization. Dietary n-3PUFA modulated breeder GIT microbiota with consequences of microbial colonization and succession in chicks. Further research has shown that feeding poultry breeders n-3 PUFA bolstered progeny immunocompetence through enhanced passive immunity and antibody titres against routine vaccination. In conclusion, it appears that chicks may benefit from the incorporation of n-3 PUFA in the breeder diets; however, little attention is paid to fatty acids composition in breeder nutrition. We also highlight gaps in knowledge and future research perspectives.